Long-Term and Transfer Effects of an Action Control Intervention in Overweight Couples: A Randomized Controlled Trial Using Text Messages - Berli, Corina; Scholz, Urte (Frontiers in Psychology, 2021)
Keeping a physically active lifestyle requires consistent self-regulatory effort such as action control (e.g., continuously monitoring and evaluating a behavior in terms of one’s goals). Involving the romantic partner in interventions might be particularly effective in the long run. The present study examined the long-term and transfer effects of an action control intervention in couples using text messaging for promoting target persons’ and partners’ physical activity, anthropometric measures and physical fitness 6 months post baseline. A total of 121 overweight and obese romantic couples, randomly allocated to an intervention (n = 60; information + action control text messages) or a control group (n = 61; information only) and to participating as target person or partner, completed baseline assessments (T1). 100 couples (82.6%) completed the 6-month follow-up (T3) assessment. Primary outcomes included self-reported moderate-to-vigorous physical activity (MVPA) and objective MVPA and MVPA adherence using triaxial accelerometers across a diary period of 14 days after T3. Secondary outcomes included BMI, waist-to-hip circumference and physical fitness (target persons only) using a submaximal aerobic cycle test. At T3, there were no significant between-group differences between target persons and partners with regard to their objective MVPA, self-reported MVPA, BMI, waist-hip ratio or physical fitness. No significant changes in outcomes were observed from T1 to T3; however, changes in BMI from T1 to T3 between target persons and partners in the intervention group were associated. Overall, the brief 14-days action control intervention was not effective in improving target person’s physical activity, body measures and physical fitness in the long-term. Moreover, no long-term benefits for partners emerged. While brief ecological momentary interventions might be a promising tool for short-term effects, future studies are needed to test features enhancing long-term effectiveness. Associations in romantic partners’ changes suggest that dyadic interventions can be a promising approach, as changes induced in one partner may then transfer over to the other (controlled-trials.com ISRCTN15705531).